線上閱讀研究之回顧與展望 Online Reading Research: A Selective Review - 劉宜芳 I-Fang Liu; 柯華葳 Hwa-Wei Ko (National Taiwan Normal University, 2017)
隨著網路的普及，線上閱讀已成為重要的生活與工作能力，其內涵複合了閱讀與資訊及通訊技術（ICT）操作，並以搜尋、評估與整合為關鍵能力。我國及許多先進國家與國際評量均已著手推動線上閱讀相關的教育政策。本文以評量研究為基礎，回顧網路興起前後，資訊、資訊及通訊技術與閱讀素養衍生的定義變革，綜觀近 20 年線上閱讀能力的研究發現，與國內中文線上閱讀相關研究，提出對未來教育與研究的展望，以期深耕國內線上閱讀教育，培養未來公民所需的能力。文獻回顧發現，國內、外研究皆顯示五到九年級學生之搜尋、評估與整合能力的表現不甚理想，且整合能力之發展有以搜尋與評估能力為基礎之趨勢。而中、小學生線上中文閱讀教學與學習困難的研究，在我國仍算少數。本文建議，未來教學研究可朝探究學生學習中文線上閱讀的困境、開發學習輔具與發展教材；教育政策面向則建議加強上述項目的教師專業培育，以及於國小高年級階段增設相關的學習指標，以利培養學生線上閱讀素養。 With the development of the Internet and digital technology, online reading abilities have become critical in daily life, including in work and education. These skills, which include information searching, evaluation, and integration, are combined with reading and ICT skills. Many countries have started to reconstruct relevant policies in reading education, and the international literacy test organization has also rebuilt the test definitions to fit this new reading environment. This paper indicates how the definitions of ICT skills and reading ability have transformed in the Internet era. Studies focusing on students' online reading skills published during the last two decades were included in the review, and Taiwan's contribution to the field was also reviewed. The literature review indicated that students from the fifth to the eighth grades did not show adequate web searching, evaluation, and integration abilities. Some studies have demonstrated that the development of integration ability might depend on web searching and evaluation abilities. Moreover, few studies have focused on Chinese online reading teaching and learning. Thus, future studies should explore instructional programs and learning difficulties to ensure students' acquisition of online reading abilities. Educators and policy-makers should support teachers to improve students' learning and establish additional guidelines for the online reading literacy curricula for fifth- and sixth-grade students.